LEGAL PHILOSOPHY AS AN ENFORCEMENT OF MORAL AND ETHICAL CHARACTER - Nasution, Iswarni; Mansar, Adi (Inspiring Law Journal, 2024)
A good law is one that can provide justice to the people it regulates. Because there is a close relationship between law and the social and cultural values of society, it is clear that good law is one that reflects the values that exist in society. aspects of legal life must always ensure that social morality, institutional morality and civil morality of citizens remain in harmony, balance and harmony. It is based on real societal values. Therefore, collaboration is very important for the formation and implementation of national social standards. Legal philosophy focuses on the goals of law, especially justice. But today, legal philosophy must study every fundamental problem of society that requires a solution. Legal experts, both theoretical and practical, who face social justice problems in everyday life, have produced a lot of legal philosophy. All of these advances show that legal philosophy plays a major role in building the paradigm of legal science, including the authority of the judiciary.